Keanekaragaman Capung (Odonata) di Kawasan Gunung Api Purba Nglanggeran Kabupaten Gunungkidul - Mega Setyawati; Triatmanto Triatmanto (Bioscientist : Jurnal Ilmiah Biologi, 2022)
This study aims to determine the types of dragonflies and the level of diversity of dragonfly species in the Nglanggeran Ancient Volcano Area, Patuk Kapanewon, Gunungkidul Regency. This research is a descriptive observational study, with accidental sampling technique. The research was conducted in March-May 2021 in the Nglanggeran Ancient Volcano Area, Patuk Kapanewon, Gunungkidul Regency. Observations were made at 08.00-16.00 WITA. The results found 11 species of dragonflies, from the Aeshnidae family 1 species (Gynacantha subinterrupta), 9 species from the Libellulidae family (Agrionoptera insignis, Diplacodes trivialis, Lathrecista asiatica, Neurothemis rambutii, Neurothemis terminata, Orthretrum sabina, Pantala flavescens, Potamarcha congener, and Zyxomma obtusum) , and 1 species from the Platycnemididae family (Copera marginipes). The diversity level of dragonflies in the Nglanggeran Ancient Volcano Region according to the Shanon-Whiener (H') diversity index is in the medium category, with a value of 1.65.